ISLAM DAN AKUNTABILITAS LINGKUNGAN: SUATU TINJAUAN TEORITIS - Khadijah Darwin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
This study aims to discuss the concept of environmental accountability and the Islamic view of environmental accountability. Environmental damage is a global problem that requires serious treatment. Environmental damage will have an impact on the survival of humans and other living things. There are demands and pressures from various stakeholders so that the company is more concerned about the environment, making the company must take steps to overcome these problems. Reporting and managing the environment are the form of corporate accountability for its operational activities that have an impact on the environment. The environmental report informs stakeholders about the company's environmental responsibility and shows the company's commitment to address environmental problems. Environmental accountability in Islam is interpreted by the prohibition of doing damage on earth, correct recording, and every action that will be accounted for. The Qur'an and the Hadith have clearly explained the importance of accountability in all areas of life. The need for accountability to fellow living beings and most importantly is accountability to Allah SWT.